Practical Significance of Transrectal Doppler Sonography and Ultrasound in Prostate Cancer - Abdukadirovich, Rakmanov Xamza (Journal of Science in Medicine and Life, 2024)
Brachytherapy allows most patients to maintain potency and reduces the risk of urinary incontinence. But here too, there are a number of nuances that do not allow brachytherapy to become the “gold standard”, including: the impossibility of correctly classifying the tumor process and determining the radicality of treatment (no sample of the prostate and lymph nodes is taken); The method is suitable only for patients with a minimal degree of the tumor process (not even for all cases of local prostate cancer). Limitations on the size of the prostate – the procedure is not suitable for patients with severe urinary tract diseases (discomfort during urination, slow urine flow, frequent urination, strong urge, repeated nighttime visits to the toilet, urinary incontinence, etc.); The postoperative period is often complicated by problems such as acute urinary retention, which requires additional therapeutic measures.